Normal supercharacter theory of the dihedral groups - Hadiseh Saydi (AUT Journal of Mathematics and Computing, 2023)
Diaconis ‎and ‎Isaacs ‎defined ‎the ‎‎supercharacter ‎theory ‎for ‎finite ‎groups ‎as a‎ ‎natural ‎generalization ‎of ‎the ‎classical ‎ordinary ‎character ‎theory ‎of ‎finite ‎groups. ‎‎Supercharacter ‎theory ‎of ‎many ‎finite ‎groups ‎such ‎as ‎the ‎cyclic ‎groups, ‎the ‎Frobenius ‎groups, ‎etc. ‎were ‎well ‎studied ‎and ‎well-known. ‎In ‎this ‎paper ‎we ‎find ‎the ‎normal ‎and ‎automorphic ‎‎supercharacter ‎theories ‎of ‎the ‎dihedral ‎groups ‎in ‎special ‎cases.‎